Retorika Ridwan Kamil Debat Calon Gubernur Pilkada DKI Jakarta 2024 - Simbolon, Ronaida Raimunda; Simanjuntak, Dairi Sapta Rindu; Tarigan, Cindy Claren Br; Harefa, Boisman; Simatupang, Dina Elfrida (Universitas Islam Sumatera Utara, 2025)
This study examines the video broadcast of the first debate of the 2024 DKI Jakarta gubernatorial candidates, aired on the TVOneNews YouTube channel under the title First Debate of the DKI Jakarta Gubernatorial Candidates. The central focus is the rhetorical analysis of the candidates’ speech during the debate. Employing a qualitative descriptive method, the research applies content analysis through listening and noting techniques to identify rhetorical patterns. The findings indicate the use of 17 distinct rhetorical devices, including alliteration, apostrophe, anaphora, antithesis, euphemism, hyperbole, irony, metaphor, and others, each serving specific persuasive functions. Additionally, the study highlights the strategic use of visual rhetoric in the video’s packaging, such as clickbait elements through image selection, bold typeface, capitalization, and punctuation in the video title to amplify audience engagement. These rhetorical and visual strategies collectively underscore ideological distinctions, persuasive intentions, and political branding efforts of the candidates. The research contributes to understanding how rhetorical expression and media presentation shape public perception and influence political discourse in digital platforms.